The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s10350-004-6255-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Dysplasia in Extensive, Long-Standing Inflammatory Bowel Disease

Abstract: Although low-grade dysplasia occurred at several colonic levels and at repeated colonoscopies in 73 percent of the patients, no progression to high-grade dysplasia was found during 10 years of follow-up, except in 2 cases with dysplasia-associated lesion or mass. Colectomy in cases with single or repeated low-grade dysplasia in flat mucosa does not appear to be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0
23

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(114 citation statements)
references
References 47 publications
0
91
0
23
Order By: Relevance
“…Lynch et al [36] identified only 2.5% of patients with LGD who went on to develop cancer. Befrits et al [59] in a study of patients with extensive longstanding colitis who were found to have fLGD on index colonoscopy, found LGD on subsequent colonoscopy in 73% of cases but none progressed to HGD except in two patients with DALM during a 10-year follow-up period. Lim et al [66] in a retrospective cohort study of patients still alive with an intact colon who had LGD, HGD, or cancer developed 10% versus 4% in patients with no LGD after 10-year follow-up.…”
Section: Proctocolectomymentioning
confidence: 98%
See 4 more Smart Citations
“…Lynch et al [36] identified only 2.5% of patients with LGD who went on to develop cancer. Befrits et al [59] in a study of patients with extensive longstanding colitis who were found to have fLGD on index colonoscopy, found LGD on subsequent colonoscopy in 73% of cases but none progressed to HGD except in two patients with DALM during a 10-year follow-up period. Lim et al [66] in a retrospective cohort study of patients still alive with an intact colon who had LGD, HGD, or cancer developed 10% versus 4% in patients with no LGD after 10-year follow-up.…”
Section: Proctocolectomymentioning
confidence: 98%
“…Thus, these lesions represent sporadic adenomas developing in areas of inflammation. Other studies have showed that ''small polyploid dysplastic lesions,'' ''pedunculated polyps,'' and lesions that endoscopically and histologically resemble an adenoma can be safely treated endoscopically with no evidence of flat dysplasia or carcinoma on follow-up provided no other areas of flat dysplasia are recognized [41,51,[58][59][60]. Adenoma-like DALM has low risk for malignancy than flat LGD (fLGD) or flat HGD [11,32,41].…”
Section: Dysplasiamentioning
confidence: 99%
See 3 more Smart Citations